Bioinspired approach to enhance mechanical properties of starch based nacre-mimetic nanocomposite. (1st October 2019) - Li, Jiali; Zhou, Mi; Cheng, Fei; Lin, Yi; Zhu, Puxin
Graphical abstract: Highlights: Dopamine was used to modify clay through its self-polymerization. Polydopamine coating benefits the dispersion of the modified clay in matrix. Polydopamine coating enhances the interfacial adhesion between the filler and matrix. Mechanical properties of the resulting nanocomposites was improved significantly. Abstract: In this work, a facile biomimetic method was proposed to enhance the interfacial adhesion between layered clay and polymer matrix inspired by strong adhesion of mussel adhesive proteins. Montmorillonite (MMT) was coated with a thin layer of polydopamine (PDA) through self-polymerization of dopamine (DA) and subsequently assembled with corn starch (CS) to generate CS/MMT-DA nanocomposite. FTIR, XPS, SEM and XRD results demonstrated that PDA coating benefited not only the intercalation and dispersion of the modified MMT (MMT-DA) in the polymer matrix but also the strong interfacial adhesion between filler and matrix. The tensile strength of CS/MMT-DA nanocomposites was largely enhanced by increasing the amount of DA or polymerization time. This work can largely expand the application of MMT and provide a new idea for preparing high performance starch nanocomposites.